Seroprevalence of SARS-CoV-2 Among Pediatric Healthcare Workers in Spain - Dacosta-Urbieta, Ana; Rivero-Calle, Irene; Pardo-Seco, Jacobo; Redondo-Collazo, Lorenzo; Salas, Antonio; Gómez-Rial, Jose; Martinón-Torres, Federico (Frontiers in Pediatrics, 2020)
Abstract Spain is one of the countries most severely affected by the SARS-CoV-2 pandemic, with almost 190,000 cases as of 18th April 2020. As healthcare workers (HCW) are one of the groups hardest hit by the infection, it is important to know the seroprevalence of antibodies against SARS-CoV-2 in Pediatric Departments. We performed 175 IgM and IgG immunocromatography rapid tests in the personnel working at the Pediatric Department of the Hospital Clínico Universitario of Santiago de Compostela (Spain), including pediatricians, residents, nurses and other staff, on days 31-33 since the lockdown started. Seven out of the 175 tests were positive, including 4 for IgM and 3 for IgG, leading to a seroprevalence of 4.0% (95%CI: 1.1-6.9). Only one of them had symptoms at the time of testing (sore throat). All seropositive cases yielded negative RT-PCR of upper and lower respiratory tract. This is the first SARS-CoV-2 serological survey among HCW reported in Spain. Notwithstanding the test limitations, our results reveal that personal protection policy and lockdown measures have been effective to limit population exposure. The low seroprevalence rate poses a significant challenge for next strategic steps of pandemic control.